The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jfpe.12942
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective process optimization for betaine enriched spelt flour based extrudates

Abstract: The main purposes of this work are successful modeling of twin‐screw extrusion process using predictive models, investigating the effect of process parameters such as screw speed, feed rate, and feed moisture content on the process and product responses and finally optimizing the process regarding betaine content in the extruded product and energy consumption. The second order polynomial approximation models and the artificial neural network were developed to predict the betaine content, showing the high accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In addition, the ANN technique permits the study of relationships between the input variables and of the outputs of the process using a limited number of experimental run (Bingöl, Hercan, Elevli, & Kılıç, 2012), being commonly applied for modeling and optimization of various processes. ANNs have been used in prediction of some parameters in various processes (Alvarez, 2009;Chakraborty & Shrivastava, 2019;Kashaninejad, Dehghani, & Kashiri, 2009;Koji c et al, 2019;Lamrini, Della Valle, Trelea, Perrot, & Trystram, 2012;Sablani, Baik, & Marcotte, 2002) and food quality evaluation (Broyart & Trystram, 2003;Funes et al, 2015;Goyache et al, 2001) or to predict dough rheological properties (farinograph peak, extensibility, and maximum resistance) from the torque developed during mixing (Ruan, Almaer, & Zhang, 1995). Other studies revealed that ANNs were used to predict the parameters of farinograph (Abbasi, Emam-Djomeh, & Seyedin, 2011), extensograph, alveograph, and fundamental rheological properties of dough from several physicochemical properties of flour (Abbasi et al, 2012;Abbasi, Emam-Djomeh, & Ardabili, 2014;Abbasi & Mohammadifar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ANN technique permits the study of relationships between the input variables and of the outputs of the process using a limited number of experimental run (Bingöl, Hercan, Elevli, & Kılıç, 2012), being commonly applied for modeling and optimization of various processes. ANNs have been used in prediction of some parameters in various processes (Alvarez, 2009;Chakraborty & Shrivastava, 2019;Kashaninejad, Dehghani, & Kashiri, 2009;Koji c et al, 2019;Lamrini, Della Valle, Trelea, Perrot, & Trystram, 2012;Sablani, Baik, & Marcotte, 2002) and food quality evaluation (Broyart & Trystram, 2003;Funes et al, 2015;Goyache et al, 2001) or to predict dough rheological properties (farinograph peak, extensibility, and maximum resistance) from the torque developed during mixing (Ruan, Almaer, & Zhang, 1995). Other studies revealed that ANNs were used to predict the parameters of farinograph (Abbasi, Emam-Djomeh, & Seyedin, 2011), extensograph, alveograph, and fundamental rheological properties of dough from several physicochemical properties of flour (Abbasi et al, 2012;Abbasi, Emam-Djomeh, & Ardabili, 2014;Abbasi & Mohammadifar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Spelt flour was extruded using co-rotating twin-screw extruder (Bühler BTSK 30/28D, 7 sections, length/diameter ratio = 28:1, Bühler, Uzwil, Switzerland). The extrusion cooking process was described previously in our work (Kojić et al 2019).…”
Section: Materials and Methods Extrusionmentioning
confidence: 99%
“…The values for the expansion index were predicted by ANN. The procedure for constructing ANN and Yoon model can be found in the paper Kojić et al (2019).…”
Section: Experimental Design and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain good network behaviour, it is necessary to make a trial and error procedure and also to choose the number of hidden layers, and the number of neurons in hidden layer(s) (20). A multi-layer perceptron model (MLP) consisted of three layers (input, hidden and output).…”
Section: Artificial Neural Network (Ann) Modellingmentioning
confidence: 99%